Weather-resistant white latex applied to wooden box bonding and preparation method thereof

By using acetalization modification and nano-silicon dioxide to enhance network structure in white latex, the problem of insufficient water resistance and moisture resistance of white latex in humid and low temperature environments is solved, and its good bonding performance and stability under different environmental conditions are achieved.

CN119823685APending Publication Date: 2025-04-15DONGGUAN MINGFENG PACKAGING CO LTD

Patent Information

Application Number
CN202411973670.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing white latex has poor water resistance and moisture resistance in humid environments, and is prone to freezing in low temperature environments, which limits its application under different environmental conditions.

Method used

Weather-resistant white latex is prepared by acetalization modification and nano-silica enhancement network structure.

Benefits of technology

It improves the water resistance, weather resistance and storage stability of white latex, so that it can maintain good bonding performance in high temperature, low temperature and high humidity environments, and avoids cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses weather-resistant white latex applied to wooden box bonding and a preparation method thereof, and the weather-resistant white latex is prepared from the following raw materials: 1 to 5 parts of polyvinyl alcohol, 20 to 45 parts of deionized water, 0.1 to 0.4 part of magnesium strengthening powder, 0.6 to 1 part of formaldehyde solution, 6 to 9.6 parts of styrene-acrylic emulsion, 0.6 to 0.96 part of hydroxypropyl methyl cellulose, 2 to 5 parts of nano silicon dioxide, 30 to 45 parts of vinyl acetate, 2 to 6 parts of acrylic acid, 2 to 6 parts of butyl acrylate and 2 to 6 parts of methyl methacrylate. The biomass fiber material comprises the following components in parts by weight: 3-6 parts of dibutyl phthalate, 0.5-2.5 parts of an emulsifier, 0.1-0.5 part of an initiator and 2-5 parts of a biomass fiber material. The white latex prepared according to the scheme provided by the invention has relatively strong weather resistance, and the white latex at the bonding part does not crack when a wooden box bonded by the white latex is placed for a period of time under the conditions of 60 DEG C, 96% humidity, 60 DEG C, 10% humidity and-20 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of white latex, and in particular discloses weather-resistant white latex used for bonding wooden boxes and a preparation method thereof. Background Art

[0002] White latex, as an environmentally friendly and efficient adhesive, plays an important role in modern life. Its wide application proves its importance in home decoration, construction, industrial manufacturing and other fields. White latex is widely popular not only because of its good bonding properties, but also because of its environmental friendliness: it is an adhesive composed entirely of water and does not contain organic solvents or other harmful substances.

[0003] Although white latex has shown great application potential in many fields, it also has some disadvantages. First, although white latex has high environmental protection characteristics, its water and moisture resistance are relatively poor. This means that when white latex is used in a humid environment, it may absorb moisture in the air and creep at high temperatures, affecting the bonding effect. In addition, white latex cannot be stored in a low temperature environment, otherwise it is prone to freezing. These problems limit the comprehensive application of white latex under different environmental conditions, especially in environments with extreme temperature changes.

[0004] Therefore, providing a weather-resistant white latex with excellent high and low temperature resistance and water resistance is a problem to be solved urgently in the prior art. Summary of the invention

[0005] The purpose of the present invention is to provide a weather-resistant white latex used for bonding wooden boxes and a preparation method thereof, so as to solve the problems mentioned in the above background technology.

[0006] On the one hand, the present invention discloses a weather-resistant white latex used for bonding wooden boxes, which adopts the following technical scheme:

[0007] The invention discloses a weather-resistant white latex for bonding wooden boxes. The raw materials used and the corresponding weight parts are as follows: 1-5 parts of polyvinyl alcohol, 20-45 parts of deionized water, 0.1-0.4 parts of magnesium powder, 0.6-1 parts of formaldehyde solution, 6-9.6 parts of styrene-acrylic emulsion, 0.6-0.96 parts of hydroxypropyl methylcellulose, 2-5 parts of nano silicon dioxide, 30-45 parts of vinyl acetate, 2-6 parts of acrylic acid, 2-6 parts of butyl acrylate, 2-6 parts of methyl methacrylate, 3-6 parts of dibutyl phthalate, 0.5-2.5 parts of emulsifier, 0.1-0.5 parts of initiator and 2-5 parts of biomass fiber material.

[0008] On the other hand, the present invention discloses a method for preparing weather-resistant white latex used for bonding wooden boxes, which adopts the following technical scheme:

[0009] A method for preparing a weather-resistant white latex used for bonding wooden boxes, which is used to prepare the weather-resistant white latex according to claim 1, comprising the following steps:

[0010] (1) According to the formula, weigh the corresponding amounts of polyvinyl alcohol, magnesium powder and deionized water into a reactor, set the reactor temperature to 90° C., turn on stirring, and react for 1.5 to 2 hours until the polyvinyl alcohol is completely dissolved;

[0011] (2) lowering the temperature of the above-mentioned reactor to 65° C., adding a corresponding amount of formaldehyde solution, stirring evenly, adjusting the pH value of the reaction liquid to 1-3, and then heating to a certain temperature for acetal reaction, continuing to stir and react for 30 minutes, then adjusting the pH value of the reaction liquid to 7-8, and at the same time lowering the temperature of the reactor to 25° C., and then adding a corresponding amount of styrene-acrylic emulsion and hydroxypropyl methylcellulose, stirring and reacting for 2 hours, and then adding a corresponding amount of nano-silicon dioxide, stirring and reacting for 1 hour, and then discharging the material to obtain a modified polyvinyl alcohol emulsion;

[0012] (3) According to the proportion, a corresponding amount of modified polyvinyl alcohol emulsion is measured and added to the reactor. The temperature is raised to 60°C while stirring, and an emulsifier is added for emulsification. Then, 15wt% of the total amount of vinyl acetate and 20wt% of the total amount of initiator are measured and reacted for 30 minutes. The reactor is then raised to a certain temperature, a corresponding amount of biomass fiber material is added, and the remaining vinyl acetate and initiator are added dropwise within 3.5 to 4 hours. The temperature is lowered to 50°C, and then a corresponding amount of dibutyl phthalate is added. The mixture is stirred evenly to obtain a weather-resistant white latex.

[0013] Preferably, the formaldehyde solution added in step (2) has a concentration of 40%, which can be replaced by acetaldehyde solution, glyoxal solution or butyraldehyde solution of equal concentration.

[0014] Preferably, in step (2), after adding dilute hydrochloric acid, the temperature is raised to carry out the acetalization reaction, and the temperature is controlled at 80-90°C.

[0015] Preferably, the styrene-acrylic emulsion added in step (2) can be replaced by styrene-butadiene emulsion; and the hydroxypropyl methylcellulose added can be replaced by hydroxyethyl methylcellulose.

[0016] Preferably, the nano-silicon dioxide added in step (2) can be replaced by nano-aluminum oxide.

[0017] Preferably, the biomass fiber material added in step (3) comprises the following raw materials in parts by weight, which are obtained by mixing and extruding granulation: 80-120 parts of starch, 10-50 parts of rice bran powder, 50-150 parts of thermoplastic resin, 0.5-10 parts of toughening agent, and 1-3 parts of lubricant.

[0018] Preferably, the emulsifier added in step (3) is sodium dodecyl sulfate or emulsifier OP-10; and the initiator is ammonium persulfate or potassium persulfate.

[0019] Preferably, in step (3), the reaction kettle is heated to a certain temperature, and then the remaining vinyl acetate is added dropwise. This part of the vinyl acetate can be replaced by a mixed solution of vinyl acetate + one or more of acrylic acid, butyl acrylate, and methyl methacrylate.

[0020] Preferably, in step (3), the reactor is heated to a certain temperature, which should be controlled at 70-85°C.

[0021] Compared with the prior art, the present invention has at least the following beneficial effects:

[0022] (1) By acetalizing polyvinyl alcohol, PVA undergoes acetalization reaction under acidic conditions to generate acetal compounds, the symmetry of the PVA molecules is destroyed, the convergence is hindered, the interaction between the hydroxyl groups on the PVA molecules and the H2O molecules is weakened, the number of hydrophilic group hydroxyl groups is reduced, and the emulsion stability and water resistance are improved;

[0023] (2) The surface of nano-silica is enriched with vinyl groups. With it as the substrate, according to the mechanism of free radical polymerization, under the action of a catalyst, the silica enriched with vinyl groups will form a covalent bond with the vinyl acetate monomer during the emulsion polymerization process, thereby forming a uniformly distributed reinforcing network structure during the preparation of the white latex. This network structure can fill the tiny pores of the matrix and prevent the penetration of water or gas, thereby improving water resistance and weather resistance. At the same time, the nano-scale particle size enables it to be evenly distributed in the emulsion, avoiding the particle agglomeration phenomenon that may occur in traditional reinforcing fillers, and improving the storage stability of the white latex. In addition, nano-silica can scatter ultraviolet rays, slow down the degradation of the white latex matrix by ultraviolet rays, enhance weather resistance, and also has high thermal stability, which can enhance the heat resistance of the white latex and delay decomposition or aging at high temperatures.

[0024] (3) Biomass fiber materials contain starch, and the hydroxyl radicals on its molecular chain are induced to be removed by the free radicals produced by the decomposition of the catalyst, forming macromolecular starch free radicals, which trigger the grafting polymerization reaction of carbon atoms with smaller steric hindrance on vinyl acetate, forming a more complex but stable structure, and improving the water resistance of the emulsion. In addition, biomass fiber materials also have high tensile strength and toughness, which can enhance the mechanical properties of the white latex matrix, thereby improving crack resistance and structural stability. This enhancement makes the white latex more stable under humid and extreme climatic conditions, indirectly improving water resistance and weather resistance. In addition, biomass fibers can also fill the micropores or defects in the white latex matrix, reducing the permeation channels of water and gas, thereby improving water resistance and anti-aging ability.

[0025] (4) The weather-resistant white latex synthesized by the above method was used to bond wooden boxes. The wooden boxes were placed under three conditions: "60°C, 96% humidity", "60°C, 10% humidity", and "-20°C". Each condition was tested for 3 days. The bonding parts did not crack, indicating good weather resistance. DETAILED DESCRIPTION

[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below in conjunction with specific implementation methods.

[0027] The weight units in the following embodiments are kg, which can actually be modified according to the proportions as required.

[0028] The raw materials involved in the following examples are all commercially available products, wherein the biomass fiber material is prepared by mixing starch, rice bran powder, thermoplastic resin, toughening agent, lubricant and other raw materials and extruding and granulating them, and is specifically prepared by the method in patent CN 106854298A.

[0029] Embodiment 1:

[0030] The invention discloses a weather-resistant white latex. The raw materials used and the corresponding weight parts thereof are as follows: 3 parts of polyvinyl alcohol, 35 parts of deionized water, 0.3 parts of magnesium powder, 0.7 parts of 40% formaldehyde solution, 8 parts of styrene-acrylic emulsion, 0.7 parts of hydroxypropyl methylcellulose, 4 parts of nano silicon dioxide, 37 parts of vinyl acetate, 5 parts of dibutyl phthalate, 2 parts of OP-10 emulsifier, 0.3 parts of ammonium persulfate and 4 parts of biomass fiber material.

[0031] The preparation method of the above-mentioned weather-resistant white latex comprises the following steps:

[0032] (1) According to the formula, weigh the corresponding amounts of polyvinyl alcohol, magnesium powder and deionized water into a reactor, set the reactor temperature to 90° C., turn on stirring, and react for about 1.5 to 2 hours until the polyvinyl alcohol is completely dissolved;

[0033] (2) lowering the temperature of the above reactor to 65°C, adding a corresponding amount of 40% formaldehyde solution, stirring for 15 minutes, then dropping 0.25 mol / L dilute hydrochloric acid until the pH value of the reaction solution is 2, then heating to 85°C for acetal reaction, continuing to stir and react for 30 minutes, then adding 8% sodium hydroxide solution to adjust the pH of the reaction solution to 7, and at the same time lowering the temperature of the reactor to 25°C, then adding a corresponding amount of styrene-acrylic emulsion and hydroxypropyl methylcellulose, stirring and reacting for 2 hours, then adding a corresponding amount of nano-silicon dioxide, stirring and reacting for 1 hour, and then discharging to obtain a modified polyvinyl alcohol emulsion;

[0034] (3) According to the proportion, take the corresponding amount of modified polyvinyl alcohol emulsion and add it to the reactor. Heat it to 60°C while stirring, add emulsifier OP-10, emulsify for 15 minutes, then take 6 parts of vinyl acetate, add 0.06 parts of initiator ammonium persulfate, and react for 30 minutes; then raise the temperature of the reactor to 80°C, add the corresponding amount of biomass fiber material, and start to drop the remaining vinyl acetate and initiator (add within 3.5 to 4 hours); cool it to 50°C, then add the corresponding amount of dibutyl phthalate, stir for 15 minutes, and you can get a white latex with good weather resistance.

[0035] Embodiment 2:

[0036] The invention discloses a weather-resistant white latex. The raw materials used and the corresponding weight parts thereof are as follows: 2.5 parts of polyvinyl alcohol, 34 parts of deionized water, 0.4 parts of magnesium powder, 0.7 parts of glyoxal solution, 8 parts of styrene-acrylic emulsion, 0.7 parts of hydroxypropyl methylcellulose, 3 parts of nano silicon dioxide, 40 parts of vinyl acetate, 4 parts of dibutyl phthalate, 2.5 parts of OP-10 emulsifier, 0.3 parts of ammonium persulfate and 4 parts of biomass fiber material.

[0037] The preparation method of the above-mentioned weather-resistant white latex comprises the following steps:

[0038] (1) According to the formula, weigh the corresponding amounts of polyvinyl alcohol, magnesium powder and deionized water into a reactor, set the reactor temperature to 90° C., turn on stirring, and react for about 1.5 to 2 hours until the polyvinyl alcohol is completely dissolved;

[0039] (2) The temperature of the above-mentioned reactor was lowered to 65° C., a corresponding amount of glyoxal solution was added, and the mixture was stirred for 15 min. Then, 0.25 mol / L dilute hydrochloric acid was added dropwise until the pH value of the reaction solution reached 2. The mixture was then heated to 90° C. for acetalization reaction. The reaction was continued with stirring for 30 min. Subsequently, 8% sodium hydroxide solution was added to adjust the pH value of the reaction solution to 7. At the same time, the temperature of the reactor was lowered to 25° C., and then a corresponding amount of styrene-acrylic emulsion and hydroxypropyl methylcellulose were added. The reaction was stirred for 2 h. Then, a corresponding amount of nano-silicon dioxide was added. The mixture was stirred for 1 h and then discharged to obtain a modified polyvinyl alcohol emulsion.

[0040] (3) According to the proportion, take the corresponding amount of modified polyvinyl alcohol emulsion and add it to the reactor. Heat it to 60°C while stirring, add emulsifier OP-10, emulsify for 15 minutes, then take 6.5 parts of vinyl acetate, add 0.06 parts of initiator ammonium persulfate, and react for 30 minutes; then raise the temperature of the reactor to 85°C, add the corresponding amount of biomass fiber material, and start to drop the remaining vinyl acetate and initiator (add within 3.5 to 4 hours); cool it to 50°C, then add the corresponding amount of dibutyl phthalate, stir for 15 minutes, and you can get a white latex with good weather resistance.

[0041] Embodiment 3:

[0042] A weather-resistant white latex, the raw materials used and the corresponding weight parts are as follows: 4 parts of polyvinyl alcohol, 35 parts of deionized water, 0.3 parts of magnesium powder, 1 part of butyraldehyde solution, 7.6 parts of styrene acrylic emulsion, 0.8 parts of hydroxypropyl methylcellulose, 5 parts of nano aluminum oxide, 34 parts of vinyl acetate, 2 parts of acrylic acid, 3 parts of dibutyl phthalate, 2 parts of OP-10 emulsifier, 0.3 parts of ammonium persulfate, and 5 parts of biomass fiber material.

[0043] The preparation method of the above-mentioned weather-resistant white latex comprises the following steps:

[0044] (1) According to the formula, weigh the corresponding amounts of polyvinyl alcohol, magnesium powder and deionized water into a reactor, set the reactor temperature to 90° C., turn on stirring, and react for about 1.5 to 2 hours until the polyvinyl alcohol is completely dissolved;

[0045] (2) lowering the temperature of the above reactor to 65°C, adding a corresponding amount of butyraldehyde solution, stirring for 15 minutes, then dropping 0.25 mol / L dilute hydrochloric acid until the pH value of the reaction solution is 2, then heating to 90°C for acetal reaction, continuing to stir and react for 30 minutes, then adding 8% sodium hydroxide solution to adjust the pH of the reaction solution to 7, and at the same time lowering the temperature of the reactor to 25°C, then adding a corresponding amount of styrene-acrylic emulsion and hydroxypropyl methylcellulose, stirring and reacting for 2 hours, then adding a corresponding amount of nano-silicon dioxide, stirring and reacting for 1 hour, and then discharging to obtain a modified polyvinyl alcohol emulsion;

[0046] (3) According to the proportion, take the corresponding amount of modified polyvinyl alcohol emulsion and add it to the reactor. Heat it to 60°C while stirring, add emulsifier OP-10, emulsify for 15 minutes, then take 5.5 parts of vinyl acetate, add 0.06 parts of initiator ammonium persulfate, and react for 30 minutes; then raise the temperature of the reactor to 85°C, add the corresponding amount of biomass fiber material, and start to drop the remaining vinyl acetate and acrylic acid mixture and initiator (add within 3.5 to 4 hours); cool it to 50°C, then add the corresponding amount of dibutyl phthalate, stir for 15 minutes, and you can get a white latex with good weather resistance.

[0047] Embodiment 4:

[0048] A weather-resistant white latex comprises the following raw materials and corresponding weight parts: 2.5 parts of polyvinyl alcohol, 33 parts of deionized water, 0.4 parts of magnesium powder, 0.6 parts of glyoxal solution, 8 parts of styrene-butadiene emulsion, 0.7 parts of hydroxyethyl methyl cellulose, 4 parts of nano silicon dioxide, 37 parts of vinyl acetate, 3 parts of butyl acrylate, 4 parts of dibutyl phthalate, 2 parts of sodium dodecyl sulfate emulsifier, 0.3 parts of ammonium persulfate and 4 parts of biomass fiber material.

[0049] The preparation method of the above-mentioned weather-resistant white latex comprises the following steps:

[0050] (1) According to the formula, weigh the corresponding amounts of polyvinyl alcohol, magnesium powder and deionized water into a reactor, set the reactor temperature to 90° C., turn on stirring, and react for about 1.5 to 2 hours until the polyvinyl alcohol is completely dissolved;

[0051] (2) The temperature of the above-mentioned reactor was lowered to 65° C., a corresponding amount of glyoxal solution was added, and the mixture was stirred for 15 min. Then, 0.25 mol / L dilute hydrochloric acid was added dropwise until the pH value of the reaction solution reached 2. The mixture was heated to 90° C. for acetalization reaction, and the reaction was continued with stirring for 30 min. Subsequently, 8% sodium hydroxide solution was added to adjust the pH value of the reaction solution to 7. At the same time, the temperature of the reactor was lowered to 25° C., and then a corresponding amount of styrene-butadiene emulsion and hydroxyethyl methylcellulose were added. The reaction was stirred for 2 h. Then, a corresponding amount of nano-silicon dioxide was added. The mixture was stirred for 1 h and then discharged to obtain a modified polyvinyl alcohol emulsion.

[0052] (3) According to the proportion, take the corresponding amount of modified polyvinyl alcohol emulsion and add it to the reactor. While stirring, heat it to 60°C, add the emulsifier sodium dodecyl sulfate, emulsify for 15 minutes, then take 6 parts of vinyl acetate, add 0.06 parts of initiator ammonium persulfate, and react for 30 minutes; then raise the temperature of the reactor to 85°C, add the corresponding amount of biomass fiber material, and start to drop the remaining vinyl acetate and butyl acrylate mixture and the initiator (add within 3.5 to 4 hours); cool it to 50°C, then add the corresponding amount of dibutyl phthalate, stir for 15 minutes, and you can get a white latex with good weather resistance.

[0053] Embodiment 5:

[0054] A weather-resistant white latex comprises the following raw materials and corresponding weight portions: 4 parts of polyvinyl alcohol, 36 parts of deionized water, 0.3 parts of magnesium powder, 1 part of butyraldehyde solution, 7.6 parts of styrene-acrylic emulsion, 0.8 parts of hydroxypropyl methylcellulose, 3 parts of nano silicon dioxide, 32 parts of vinyl acetate, 2.5 parts of acrylic acid, 2.5 parts of butyl acrylate, 3 parts of dibutyl phthalate, 2 parts of OP-10 emulsifier, 0.3 parts of ammonium persulfate and 3 parts of biomass fiber material.

[0055] The preparation method of the above-mentioned weather-resistant white latex comprises the following steps:

[0056] (1) According to the formula, weigh the corresponding amounts of polyvinyl alcohol, magnesium powder and deionized water into a reactor, set the reactor temperature to 90° C., turn on stirring, and react for about 1.5 to 2 hours until the polyvinyl alcohol is completely dissolved;

[0057] (2) lowering the temperature of the above-mentioned reactor to 65°C, adding a corresponding amount of butyraldehyde solution, stirring for 15 minutes, and then dropping 0.25 mol / L dilute hydrochloric acid until the pH value of the reaction solution is 2; then heating to 90°C for acetal reaction, continuing to stir and react for 30 minutes, then adding 8% sodium hydroxide solution to adjust the pH of the reaction solution to 7, and at the same time lowering the temperature of the reactor to 25°C, and then adding a corresponding amount of styrene-acrylic emulsion and hydroxypropyl methylcellulose, stirring and reacting for 2 hours, and then adding a corresponding amount of nano-silicon dioxide, stirring and reacting for 1 hour, and then discharging to obtain a modified polyvinyl alcohol emulsion;

[0058] (3) According to the proportion, take the corresponding amount of modified polyvinyl alcohol emulsion and add it to the reactor. Heat it to 60°C while stirring, add emulsifier OP-10, emulsify for 15 minutes, then take 5 parts of vinyl acetate, add 0.06 parts of initiator ammonium persulfate, and react for 30 minutes; then raise the temperature of the reactor to 85°C, add the corresponding amount of biomass fiber material, and start to drop the remaining vinyl acetate, acrylic acid and butyl acrylate mixture and initiator (add within 3.5 to 4 hours); cool it to 50°C, then add the corresponding amount of dibutyl phthalate, stir for 15 minutes, and you can get a white latex with good weather resistance.

[0059] Comparative Example 1:

[0060] A weather-resistant white latex comprises the following raw materials and corresponding weight parts: 4 parts of polyvinyl alcohol, 44.9 parts of deionized water, 0.3 parts of magnesium powder, 45 parts of vinyl acetate, 3 parts of dibutyl phthalate, 2.5 parts of OP-10 emulsifier and 0.3 parts of ammonium persulfate.

[0061] The preparation method of the above-mentioned weather-resistant white latex comprises the following steps:

[0062] (1) According to the formula, weigh the corresponding amounts of polyvinyl alcohol, magnesium powder and deionized water into a reactor, set the reactor temperature to 90° C., turn on stirring, and react for about 1.5 to 2 hours until the polyvinyl alcohol is completely dissolved;

[0063] (2) According to the proportion, take the corresponding amount of polyvinyl alcohol emulsion and add it to the reactor. Heat it to 60°C while stirring. Add emulsifier OP-10 and emulsify for 15 minutes. Then take 7 parts of vinyl acetate and add 0.06 parts of initiator ammonium persulfate. React for 30 minutes. Then raise the reactor to 85°C and start to drop the remaining vinyl acetate and initiator (add them within 3.5 to 4 hours). Cool it to 50°C, then add the corresponding amount of dibutyl phthalate and stir for 15 minutes to obtain white latex.

[0064] Comparative Example 2:

[0065] A weather-resistant white latex comprises the following raw materials and corresponding weight parts: 3 parts of polyvinyl alcohol, 42 parts of deionized water, 0.3 parts of magnesium powder, 8 parts of styrene acrylic emulsion, 0.9 parts of hydroxypropyl methylcellulose, 40 parts of vinyl acetate, 3 parts of dibutyl phthalate, 2.5 parts of OP-10 emulsifier and 0.3 parts of ammonium persulfate.

[0066] The preparation method of the above-mentioned weather-resistant white latex comprises the following steps:

[0067] (1) According to the formula, weigh the corresponding amounts of polyvinyl alcohol, magnesium powder and deionized water into a reactor, set the reactor temperature to 90° C., turn on stirring, and react for about 1.5 to 2 hours until the polyvinyl alcohol is completely dissolved;

[0068] (2) adding corresponding amounts of styrene acrylic emulsion and hydroxypropyl methylcellulose, stirring and reacting for 2 hours, and then discharging the mixture to obtain a modified polyvinyl alcohol emulsion;

[0069] (3) According to the proportion, take the corresponding amount of modified polyvinyl alcohol emulsion and add it to the reactor. Heat it to 60°C while stirring. Add emulsifier OP-10 and emulsify for 15 minutes. Then take 6.5 parts of vinyl acetate and add 0.06 parts of initiator ammonium persulfate. React for 30 minutes. Then raise the reactor to 85°C and start to drop the remaining vinyl acetate and initiator (add them within 3.5 to 4 hours). Cool it to 50°C, then add the corresponding amount of dibutyl phthalate and stir for 15 minutes to obtain white latex.

[0070] Comparative Example 3:

[0071] A weather-resistant white latex, the raw materials used and the corresponding weight parts are as follows: 3 parts of polyvinyl alcohol, 45.2 parts of deionized water, 0.3 parts of magnesium powder, 0.7 parts of 40% formaldehyde aqueous solution, 45 parts of vinyl acetate, 3 parts of dibutyl phthalate, 2.5 parts of OP-10 emulsifier, 0.3 parts of ammonium persulfate.

[0072] The preparation method of the above-mentioned weather-resistant white latex comprises the following steps:

[0073] (1) According to the formula, weigh the corresponding amounts of polyvinyl alcohol, magnesium powder and deionized water into a reactor, set the reactor temperature to 90° C., turn on stirring, and react for about 1.5 to 2 hours until the polyvinyl alcohol is completely dissolved;

[0074] (2) lowering the temperature of the above reactor to 65° C., adding a corresponding amount of 40% formaldehyde solution, stirring for 15 min, then dropping 0.25 mol / L dilute hydrochloric acid until the pH value of the reaction solution is 2, then raising the temperature to 85° C. for acetal reaction, continuing to stir and react for 30 min, then adding 8% sodium hydroxide solution to adjust the pH of the reaction solution to 7, and at the same time lowering the temperature of the reactor to 25° C., stirring and reacting for 2 h, and then discharging the material to obtain a modified polyvinyl alcohol emulsion;

[0075] (3) According to the proportion, take the corresponding amount of modified polyvinyl alcohol emulsion and add it to the reactor. Heat it to 60°C while stirring. Add emulsifier OP-10 and emulsify for 15 minutes. Then take 7 parts of vinyl acetate and add 0.06 parts of initiator ammonium persulfate. React for 30 minutes. Then raise the reactor to 85°C and start to drop the remaining vinyl acetate and initiator (add them within 3.5 to 4 hours). Cool it to 50°C, then add the corresponding amount of dibutyl phthalate and stir for 15 minutes to obtain white latex.

[0076] Comparative Example 4:

[0077] A weather-resistant white latex comprises the following raw materials and corresponding weight parts: 3 parts of polyvinyl alcohol, 43.9 parts of deionized water, 0.3 parts of magnesium powder, 4 parts of nano silicon dioxide, 43 parts of vinyl acetate, 3 parts of dibutyl phthalate, 2.5 parts of OP-10 emulsifier and 0.3 parts of ammonium persulfate.

[0078] The preparation method of the above-mentioned weather-resistant white latex comprises the following steps:

[0079] (1) According to the formula, weigh the corresponding amounts of polyvinyl alcohol, magnesium powder and deionized water into a reactor, set the reactor temperature to 90° C., turn on stirring, and react for about 1.5 to 2 hours until the polyvinyl alcohol is completely dissolved;

[0080] (2) adding a corresponding amount of nano-silicon dioxide, stirring and reacting for 1 hour, and then discharging the material to obtain a modified polyvinyl alcohol emulsion;

[0081] (3) According to the proportion, take the corresponding amount of modified polyvinyl alcohol emulsion and add it to the reactor. Heat it to 60°C while stirring. Add emulsifier OP-10 and emulsify for 15 minutes. Then take 7 parts of vinyl acetate and add 0.06 parts of initiator ammonium persulfate. React for 30 minutes. Then raise the reactor to 85°C and start to drop the remaining vinyl acetate and initiator (add them within 3.5 to 4 hours). Cool it to 50°C, then add the corresponding amount of dibutyl phthalate and stir for 15 minutes to obtain white latex.

[0082] Comparative Example 5

[0083] A weather-resistant white latex comprises the following raw materials and corresponding weight parts: 3 parts of polyvinyl alcohol, 43.9 parts of deionized water, 0.3 parts of magnesium powder, 43 parts of vinyl acetate, 3 parts of dibutyl phthalate, 2.5 parts of OP-10 emulsifier, 0.3 parts of ammonium persulfate and 4 parts of biomass fiber material.

[0084] The preparation method of the above-mentioned weather-resistant white latex comprises the following steps:

[0085] (1) According to the formula, weigh the corresponding amounts of polyvinyl alcohol, magnesium powder and deionized water into a reactor, set the reactor temperature to 90° C., turn on stirring, and react for about 1.5 to 2 hours until the polyvinyl alcohol is completely dissolved;

[0086] (2) According to the proportion, take the corresponding amount of polyvinyl alcohol emulsion and add it to the reactor. Heat it to 60°C while stirring. Add emulsifier OP-10 and emulsify for 15 minutes. Then take 7 parts of vinyl acetate and add 0.06 parts of initiator ammonium persulfate. React for 30 minutes. Then raise the reactor to 85°C, add the corresponding amount of biomass fiber material, and start to drop the remaining vinyl acetate and initiator (add within 3.5 to 4 hours). Cool it to 50°C, then add the corresponding amount of dibutyl phthalate and stir for 15 minutes to obtain white latex.

[0087] After the white latex synthesized according to the above embodiments and comparative examples was used for bonding wooden boxes, the bonded wooden boxes were placed under the conditions of "60°C, 96% humidity", "60°C, 10% humidity" and "-20°C" for 72 hours each, and the conditions of the bonding parts were observed. The results are shown in Table 1.

[0088] Table 1

[0089]

[0090] From the test results in Table 1, it can be seen that the white latex prepared in Examples 1-5 will not crack at the bonding sites when placed under the conditions of "60°C, 96% humidity", "60°C, 10% humidity" and "-20°C" for a period of time, indicating that it has excellent weather resistance at high or low temperatures and good water resistance at high humidity.

[0091] Comparative Example 1 is a traditional white latex formula on the market and its preparation method. Although the wooden box does not crack under high temperature and low humidity, it will show different degrees of wooden box cracking under high temperature, high humidity and low temperature. Comparative Example 2 adds styrene acrylic emulsion on the basis of Comparative Example 1; Comparative Example 3 adds 40% formaldehyde solution on the basis of Comparative Example 1; Comparative Example 4 adds nano silicon dioxide on the basis of Comparative Example 1; Comparative Example 5 adds biomass fiber material on the basis of Comparative Example 1; Example 1 adds styrene acrylic emulsion, 40% formaldehyde solution, nano silicon dioxide and biomass fiber material on the basis of Comparative Example 1. Although Comparative Examples 2-4 have a certain degree of performance improvement compared to Comparative Example 1 under high temperature and high humidity conditions, the performance improvement is not obvious under low temperature conditions. Example 1 not only exhibits good anti-cracking effect under high temperature and high humidity conditions, but also has a significant performance improvement compared to Comparative Example 1 under low temperature conditions, proving that the acetalization modification of polyvinyl alcohol has a synergistic gain effect with the addition of several important raw materials, such as styrene acrylic emulsion, nano-silica and biomass fiber materials. The white latex prepared by the scheme provided by the present invention, such as Examples 1-5, can take into account high temperature resistance, water resistance and cold resistance.

[0092] The technical solution provided by the present invention is introduced in detail above. Specific examples are used in this article to illustrate the principle and implementation mode of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of ​​the present invention, there will be changes in the specific implementation mode and application scope. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A weather-resistant white latex used for bonding wooden boxes, characterized in that: The raw materials used and their corresponding weight parts are as follows: 1-5 parts of polyvinyl alcohol, 20-45 parts of deionized water, 0.1-0.4 parts of magnesium powder, 0.6-1 parts of formaldehyde solution, 6-9.6 parts of styrene-acrylic emulsion, 0.6-0.96 parts of hydroxypropyl methylcellulose, 2-5 parts of nano silicon dioxide, 30-45 parts of vinyl acetate, 2-6 parts of acrylic acid, 2-6 parts of butyl acrylate, 2-6 parts of methyl methacrylate, 3-6 parts of dibutyl phthalate, 0.5-2.5 parts of emulsifier, 0.1-0.5 parts of initiator and 2-5 parts of biomass fiber material.

2. A method for preparing a weather-resistant white latex for bonding wooden boxes, which is used to prepare the weather-resistant white latex according to claim 1, characterized in that: The following steps are involved: (1) According to the formula, weigh the corresponding amounts of polyvinyl alcohol, magnesium powder and deionized water into a reactor, set the reactor temperature to 90° C., turn on stirring, and react for 1.5 to 2 hours until the polyvinyl alcohol is completely dissolved; (2) lowering the temperature of the above-mentioned reactor to 65° C., adding a corresponding amount of formaldehyde solution, stirring evenly, adjusting the pH value of the reaction liquid to 1-3, and then heating to a certain temperature for acetal reaction, continuing to stir and react for 30 minutes, then adjusting the pH value of the reaction liquid to 7-8, and at the same time lowering the temperature of the reactor to 25° C., and then adding a corresponding amount of styrene-acrylic emulsion and hydroxypropyl methylcellulose, stirring and reacting for 2 hours, and then adding a corresponding amount of nano-silicon dioxide, stirring and reacting for 1 hour, and then discharging the material to obtain a modified polyvinyl alcohol emulsion; (3) According to the proportion, a corresponding amount of modified polyvinyl alcohol emulsion is measured and added to the reactor. The temperature is raised to 60°C while stirring, and an emulsifier is added for emulsification. Then, 15wt% of the total amount of vinyl acetate and 20wt% of the total amount of initiator are measured and reacted for 30 minutes. The reactor is then raised to a certain temperature, a corresponding amount of biomass fiber material is added, and the remaining vinyl acetate and initiator are added dropwise within 3.5 to 4 hours. The temperature is lowered to 50°C, and then a corresponding amount of dibutyl phthalate is added. The mixture is stirred evenly to obtain a weather-resistant white latex.

3. The method for preparing the weather-resistant white latex for bonding wooden boxes according to claim 2, characterized in that: The formaldehyde solution added in step (2) can be replaced by acetaldehyde solution, glyoxal solution or butyraldehyde solution.

4. The method for preparing the weather-resistant white latex for bonding wooden boxes according to claim 2, characterized in that: In step (2), after adding dilute hydrochloric acid, the temperature is raised to carry out acetalization reaction, and the temperature is controlled at 80-90°C.

5. The method for preparing the weather-resistant white latex for bonding wooden boxes according to claim 2, characterized in that: The styrene-acrylic emulsion added in step (2) can be replaced by styrene-butadiene emulsion; the hydroxypropyl methylcellulose added can be replaced by hydroxyethyl methylcellulose.

6. The method for preparing the weather-resistant white latex for bonding wooden boxes according to claim 2, characterized in that: The nano-silicon dioxide added in step (2) can be replaced by nano-aluminum oxide.

7. The method for preparing the weather-resistant white latex for bonding wooden boxes according to claim 2, characterized in that: The biomass fiber material added in step (3) comprises the following raw materials in parts by weight, which are prepared by mixing and extruding granulation: 80-120 parts of starch, 10-50 parts of rice bran powder, 50-150 parts of thermoplastic resin, 0.5-10 parts of toughening agent, and 1-3 parts of lubricant.

8. The method for preparing the weather-resistant white latex for bonding wooden boxes according to claim 2, characterized in that: The emulsifier added in step (3) is sodium dodecyl sulfate or emulsifier OP-10; the initiator is ammonium persulfate or potassium persulfate.

9. The method for preparing the weather-resistant white latex for bonding wooden boxes according to claim 2, characterized in that: In step (3), the reaction kettle is heated to a certain temperature, and then the remaining vinyl acetate is added dropwise. This part of the vinyl acetate can be replaced by a mixed solution of vinyl acetate + one or more of acrylic acid, butyl acrylate, and methyl methacrylate.

10. The method for preparing the weather-resistant white latex for bonding wooden boxes according to claim 2, characterized in that: In step (3), the reaction kettle is heated to a certain temperature, which should be controlled at 70-85°C.

Citation Information

Patent Citations

  • Degradable biomass and fiber composite material, and preparation method and packaging product thereof

    CN106854298A

Cited By

  • Weather-resistant white emulsion for wood box bonding and preparation method thereof

    CN122790572A